An Exploratory Study of Managers' Perspective of Work‐Life Balance in Nigeria: A Case Analysis of the Nigerian Banking Sector1. (19th December 2012) - Mordi, Chima; Mmieh, Frederick; Ojo, Stella Ibiyinka
Abstract This study describes an exploratory research of managers' perspective of the concept of work‐life balance (WLB) policies and practices in Nigeria. This is done through in‐depth case studies of 20 banks in the banking sector. The data set is comprised of responses from 102 middle line managers in the Nigerian banking institutions. A review of the extant literature on WLB initiatives in the banking sector revealed that there is a dearth of knowledge on WLB policies and practices in an African context. In an attempt to fill the gap in the literature, this study examines the range and scope of WLB practices, managers' perception of WLB, and the forces helping or constraining to shape the choices of work life balance practices and policies. The findings reveal that there is diversity in terms of how middle‐line managers understand and experience WLB initiatives in Nigeria. Another finding highlights the practice of favoritism in most banks using WLB initiatives. In addition, the study shows that cultural sensitivity affects how WLB is appreciated and utilized. The study suggests some policy implications in the form of support for WLB policies in this context. © 2013 Crown copyright.